Sustainable Synergy Governance and Community Agency in Pokland Asset-Based Ecotourism - Ridwan Iskandar; Retno Budi Wahyuni; Nandang Suhada Yasir Mansyur; Moch. Agus Syadad Saefullah; Odang Rusmana (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study examines the transformation of community agency through the Social Forestry Business Group (KUPS) scheme in Wana Wisata Pokland, Cianjur. Using a qualitative case study approach informed by the Asset-Based Community Development (ABCD) framework, this research explores the role of institutional legality in shaping empowerment processes. Data were collected through in-depth interviews with 30 informants and validated through triangulation and member checking. The findings suggest that the KUPS scheme has facilitated the reconfiguration of forest space into value-added environmental services, contributing to improved livelihood stability and enhanced community participation. In addition, many informants reported experiencing psychological empowerment through formal recognition of their roles as ecotourism leader.The study also identifies several challenges, including uneven benefit distribution, risks of internal elitism, and environmental management issues such as waste handling during peak tourism periods. While studies on community-based tourism (CBT) are well established, a theoretical gap remains in understanding how community identity transforms from forest  into formally recognized conservation partners under state-regulated frameworks. This study proposes the Sustainable Synergy Governance Model as a conceptual framework that integrates local asset mobilization with institutional mechanisms, highlighting the importance of balancing conservation objectives with community-based economic resilience.